Theoretical and parametric studies of a self-centering modular steel structure connection. (15th November 2021) - Zhang, Ge; Xu, Long-He; Li, Zhong-Xian
Highlights: A novel modular steel structure (MSS) connection using symmetrical self-centering (SC) haunch braces is proposed. Theoretical model of SC-MSS connection is established to evaluate the haunching effects. SC-MSS connection exhibits satisfactory bearing capacity and self-centering capability. Hysteretic behavior of SC-MSS connection are studied through comprehensive parameter analyses. Abstract: A novel modular steel structure (MSS) connection using symmetrical self-centering (SC) haunch braces is proposed to expand the current research limits and create a modular structure with superior seismic resilient performance and functional recoverability after earthquakes. An advanced connection technique of the modules consisting of a cross-shaped plug-in connector, cover plates, and several bolts is used to provide adequate stiffness and ensure structural integrity. A theoretical model of the self-centering MSS (SC-MSS) connection system is established to evaluate the haunch brace effects on the key components, and the model is validated by simulations. The effects of the dimension of the plug-in connector, the location and performance parameters of the SC haunch brace, and the haunch brace configuration on the seismic resilient performance of the connection are analyzed. The SC-MSS connections exhibit satisfactory self-centering capability, and the bearing capacity is substantially higher than that of the MSS connection. A large tenon height in the connector increases the local strength of the column flanges, ensuring the ductile failure mode in areas of concentrated plasticity in the beams. As the installation distance, angle and pre-stressed force of the SC haunch brace increases, the bearing capacity and self-centering capability of the connection are effectively improved. The stable and expected behavior of the connection with the non-symmetrical haunch configuration demonstrates the feasibility of the independent selection of the haunch patterns of each module. The additional strength and stiffness provided by the SC haunch braces result in acceptable energy dissipation of the SC-MSS connection and significant damage reduction.